CF3-substituted carbocations: underexploited intermediates with great potential in modern synthetic chemistry - Fernandes, Anthony J.; Panossian, Armen; Michelet, Bastien; Martin-Mingot, Agnès; Leroux, Frédéric R.; Thibaudeau, Sébastien (Beilstein Journal of Organic Chemistry, 2021)
“The extraordinary instability of such an “ion” accounts for many of the peculiarities of organic reactions” – Franck C. Whitmore (1932). This statement from Whitmore came in a period where carbocations began to be considered as intermediates in reactions. Ninety years later, pointing at the strong knowledge acquired from the contributions of famous organic chemists, carbocations are very well known reaction intermediates. Among them, destabilized carbocations – carbocations substituted with electron-withdrawing groups – are, however, still predestined to be transient species and sometimes considered as exotic ones. Among them, the CF3-substituted carbocations, frequently suggested to be involved in synthetic transformations but rarely considered as affordable intermediates for synthetic purposes, have long been investigated. This review highlights recent and past reports focusing on their study and potential in modern synthetic transformations.
Keywords: carbocation; organic synthesis; superelectrophile; trifluoromethyl